MODERNIZATION LAW AS A CRIME CORRUPTION VERY EXCEPTIONAL THROUGH ENFORCEMENT OF ETHICS - Sukresno Sukresno (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
In this era of modernization of every country are not directly have the same definition that corruption as a form of crime that is extraordinary (Extra-ordinary crime). Similarity orupsi definition of the offenses is one of them motivated by implication posed a systemic nature and sustainability on corruption. However, in practice many countries in the world use the shortcut in conducting countermeasures against corruption which one of them through the efforts of law enforcement or form. Whereas in the practical level, the form of law enforcement in resolving corruption are often not cut the chain of corruption developments actually make corruption is getting stronger. As an alternative enforcement etikan is a right step in which the main principles of ethics enforcement is prevention so that the chain will not be endemic corruption. As a form of penagakan ethical justification for decent doiterapkan given the tendency of ethics violation is a violation of the law, so that through the enforcement of ethical corruption will be lost in such a manner.   Keywords: Law Enforcement, Corruption And Ethics